Patents and fundamental rights in U.S. law: Excessive drug pricing as an instance of Unfair Competition - Jin, E (2020)
The United States suffers from a “resource curse” of essential medicines. It has great industrial and commercial capacity to meet the essential medicine needs of its citizens, yet by and large, average consumers struggle to obtain the drugs on which they depend to maintain a subsistence level of health due to the exorbitant drug pricing. As a result, they face a dilemma between paying the prices charged for access to the drugs or continued ill health. I believe that denying access to essential medicines on reasonable terms constitutes a form of injury to them. This thesis conceives of restrictive access’s injurious effects on consumers as a legal harm and sees its lack of recognition in law as an explanation for the problem’s continued existence. Traditional legal restrictions on patentee conduct, based on principles of patent misuse and antitrust, are unable to properly address this injury. While this might suggest a need for legal reform, there exists another solution almost entirely overlooked by commentators. This solution is the law of unfair competition, specifically its Unfairness Doctrine. In this thesis, I argue that the Unfairness Doctrine supports a tort-based cause of action against those who rely on patent rights to exclude consumers from access to essential medicines on reasonable terms. As such exclusion causes harm to consumers’ autonomy and bodily integrity, I further argue that even if the Unfairness Doctrine does not apply, the nature of this harm, combined with the duty of the state to protect the fundamental rights of its citizens, supports legal intervention to prevent the excessive pricing of essential medicines.